Proposed improvement in social studies instruction at the Jose Rizal College High School - Cacapit, Marina Q. 1949- (1979)
This study was designed to find out the extent to which the perceptions of the students and teachers of social studies instruction at the Jose Rizal College High School would need immediate and future innovations. The writer used the empirical and descriptive method of gathering data. The study concluded that both teachers and students have a high regard for social studies. The teachers seemed to be indefinite as to the usefulness of the subject areas to the lives of the students. The students, however, pinpoint Social Studies as useful now and Mathematics in the future. Although there is a demand for an elimination of some subject areas in social studies, there is also an expressed desire to add social science courses which would enrich the social studies curriculum and encourage in-depth study and content selection.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines -- Mandaluyong City; Social science teachers -- Philippines -- Mandaluyong City